The vile village - Snicket, Lemony; Helquist, Brett (New York HarperCollins, 2001)
Under a new government program based on the saying "It takes a village to raise a child," the Baudelaire orphans are adopted by an entire town, with disastrous results.
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; City and town life -- Fiction; Humorous stories